Väkivallan tekijöiden mieskuvat sekä terapeuttien vastaustavat niihin Vaihtoehto väkivallalle -ryhmäinterventiossa - Fågel, Lotta; Rasinkangas, Sanni (2024)
The aim of this study is to examine the representations of men which were constructed by perpetrators of intimate partner violence in a batterer intervention program. The representation of men refers to perceptions and beliefs about masculinity. In addition, we will examine therapists' response modes to the constructed representations of men. We approach the topic from the grounding theory of social constructionism as well as from a feminist framework. We emphasize the connection between language and the surrounding society, and we understand intimate partner violence as an instrument of control that stems from gender inequality. Studying the representations of men is relevant because the discursive nature of language implies that attitudes, beliefs and tasks associated with masculinity are known to influence men's behavior. Representations of men can influence the use of violence and therefore it is important to take them into account in batterer intervention programs. It is also essential to focus attention on how therapists respond to them. Through their responses, therapists can contribute to the construction of representations of men and support the process of liberating from harmful perceptions. The data of our study consists of 18 group sessions of the Alternative to Violence intervention, which was carried out in cooperation between the Crisis Centre Mobile and the University of Jyväskylä Psychotherapy Training and Research Centre. The participants are therapists and men who attended the group in 2017–2019. The group members are Finnish men who have used violence in their intimate relationships. We used discourse analysis as a research method. We found six different representations of men: the man who restrains his emotions, the man in charge, the superior man, the honorable man, the man who subjugates women and the man who opposes traditional masculinity. The therapists responded to the constructed representations of men using a variety of response modes, mainly using a supportive approach. The responses had very little confrontation of constructed perceptions. The representations of men were mainly based on traditional conceptions of masculinity and hegemonic masculinity, which previous research has found to be associated with violence. Representations of men, which emphasize male dominance, maintain unequal power structures in society. Our findings provide new insights into representations of violent men and the construction of interactions in the context of group intervention. Our results can be used to develop the Alternative to Violence intervention and other perpetrator intervention programs. To reduce intimate partner violence, representations of men should be addressed more in perpetrator interventions. In addition, our results show the potential for utilizing representations of men in violence prevention.